ANALISIS ALOKASI BIAYA OVERHEAD PABRIK ATAS PENENTUAN HARGA POKOK PRODUKSI PADA TOTO ATE MEUBEL DI DESA TENDATOTO KECAMATAN WOLOWAE KABUPATEN NAGEKEO - Noni, Agriana; Thalib, Sabra B Wahab; Banda, Falentina Lucia (Program Studi Akuntansi Universitas Flores, 2023)
he purpose of this study was to determine the allocation of factory overhead costs in determining the cost of production at Toto Ate Furniture in Tendatoto Village, Wolawae District, Nagekeo Regency. The data analysis technique used is descriptive qualitative analysis of data collected, compiled, grouped and analyzed so that it can provide an actual picture of the allocation of factory overhead costs in determining the cost of production at Toto Ate Furniture in Tendatoto Village, Wolowae District, Nagekeo Regency. The results of this study indicate that (1) production costs at Toto Ate Meubel are not actual costs, which do not include distribution costs in calculating the cost of production. (2) There is a significant difference between the calculation of the cost of production that has been carried out by Toto Ate Meubel, and the calculation of the cost of production that should have been done. (3) BOP loading based on the direct labor cost method obtained a percentage of 49% of the total direct labor cost.